GhMYB102 promotes drought resistance by regulating drought-responsive genes and ABA biosynthesis in cotton (Gossypium hirsutum L.). (April 2023) - Liu, Ruida; Shen, Yanhui; Wang, Minxuan; Liu, Ruihua; Cui, Ziqian; Li, Pengzhen; Wu, Qidi; Shen, Qian; Chen, Jing; Zhang, Siping; Liu, Shaodong; Ma, Huijuan; et al.
Abstract: The MYB transcription factor (TF) family is among the largest TF families and plays an important role in plant growth and stress response. However, few studies have investigated the role of the MYB gene in drought resistance in cotton. In this study, we analysed the drought transcriptomic data of cotton and identified that the GhMYB102 gene was significantly upregulated in upland cotton during the early stages of drought stress. Bioinformatics analysis showed that the amino acid sequence encoded by GhMYB102 contained two highly conserved MYB binding domains belonging to R2R3-MYB TFs. GhMYB102 was most closely related to AtMYB102 . GhMYB102 is mainly expressed in roots and is induced by abiotic stresses and abscisic acid (ABA); it is localised in the nucleus and has transcriptional activation activity. Silencing of GhMYB102 decreased plant drought resistance. In addition, dual-luciferase assays and yeast single hybridisation analysis showed that GhMYB102 could directly bind the MYB motif elements in the promoter regions of GhNCED1 and GhZAT10 . These results indicate that GhMYB102 plays a positive role in drought tolerance by regulating the expression of GhNCED1 and GhZAT10 . Thus, GhMYB102 enhances drought resistance by participating in ABA biosynthesis or regulating the expression of drought-responsive genes. Highlights: Drought resistance transcription factors were screened from drought transcriptome. Functional validation of MYB transcription factors under drought stress in plants. MYB transcription factors regulates plant drought tolerance by regulating ABA synthesis. Drought-responsive genes regulated by MYB transcription factors.